The Impact of COVID-19 Lockdown on Pediatric Hospital Admissions in Turkey - Erdede, Ozlem; Sarı, Erdal; Uygur Külcü, Nihan; Sezer Yamanel, Rabia Gönül (Journal of Pediatric Infectious Diseases, 2022)
Objective Health care utilization has declined significantly during the coronavirus disease 2019 (COVID-19) pandemic. We aimed to analyze the impact of COVID-19 lockdowns on pediatric admissions in a Turkish medical center.Methods This retrospective study was conducted by analyzing the numbers and records, including diagnoses, of patients admitted to our pediatric department between March 11, 2020 (the day of the first confirmed COVID-19 case in Turkey) and June 11, 2020 and comparing it with the diagnoses and numbers for the same period in 2019. The most common reasons for admissions were investigated.Results Totally, 89,607 patients were included. Patient visits reduced drastically by 63.11 to 36.89% during the lockdown period compared to the preceding year. In addition to the impact of COVID-19 lockdowns on the total volume of patients, we observed significant variations in the distribution of diagnoses among children. The percentage of respiratory, gastrointestinal, immunological, and ophthalmologic diseases and allergic reactions statistically decreased (p < 0.001). In contrast, the relative percentage of neonatal, urogenital, neurological, cardiovascular, hematological, and dermatological diseases significantly increased (p < 0.001) among emergency department (ED) admissions. Notably, the percentage of respiratory diseases among ED patients decreased by 66.81 to 33.19%.Conclusion COVID-19 strongly affected health care utilization. The public must be educated about the safety of hospital environments, and families should be encouraged to visit hospitals in case of emergencies. Additionally, changes in public health advice may help alter health care consumption patterns.
Keywords: COVID-19; children; public health; health care utilization; Turkey